Classroom Assessment - W. Airasian Peter (Mc Graw Hill, 2007)
Classroom Assessment: Concepts and Applications views classroom assessment as an everyday, ongoing part of teaching, integral to everything that happens in the classroom. The text is organized to follow the natural progression of teacher decision making, from organizing the class as a learning community to planning and conducting instruction to the formal evaluation of learning and, finally, to grading. Classroom Assessment presents complex concepts clearly so that pre-service teachers can understand them, and solidly grounds these concepts in best practice through practical, well-integrated examples. The text conceives of classroom assessment in a broader way than many other texts. It focuses not only on the assessment needs of testing, grading, interpreting standardized tests, and performance assessments but also on assessment concerns in organizing a classroom at the start of school, planning and implementing instruction, and strategies of teacher self reflection.